Effects of front-of-package caffeine and sweetener disclaimers in Mexico: cross-sectional results from the 2020 International Food Policy Study - Laura Patricia Arellano-Gómez; Alejandra Jáuregui; Claudia Nieto; Alejandra Contreras-Manzano; Kathia Larissa Quevedo; Christine M White; James F Thrasher; Rachel E Davis; David Hammond; Simón Barquera (Cambridge University Press, 2023)
Abstract Objective: Front-of-package warning labels introduced in Mexico in 2020 included disclaimers that caution against allowing children to consume products with non-sugary sweeteners and caffeine. We examined the awareness and use of the disclaimers among Mexican adults and youth 1 month after the regulation was implemented. We also investigated their impact on the perceived healthfulness of industrialised beverages designed for children. Design: Data on the awareness and use of the disclaimers were analysed. Two between-subjects experiments examined the effect of a sweetener disclaimer (Experiment 1, youth and adults) or a caffeine disclaimer (Experiment 2, only adults) on the perceived healthfulness of industrialised beverages. Interactions between experimental conditions and demographic characteristics were tested. Setting: Online survey in 2020. Participants: Mexican adults (≥18 years, n 2108) and youth (10-17 years, n 1790). Results: Most participants (>80 %) had seen the disclaimers at least rarely, and over 60 % used them sometimes or frequently. The sweetener disclaimer led to a lower perceived healthfulness of a fruit drink (adults: 2·74 ± 1·44; youth: 2·04 ± 0·96) compared with the no-disclaimer condition (adults: 3·17 ± 1·54; youth: 2·32 ± 0·96) (t's: >4·0, P values: <0·001). This effect was larger among older adults and male youth. The caffeine disclaimer did not affect adult's perceived healthfulness of a caffeinated drink (t = 0·861, P value = 0·3894). Conclusions: There were high awareness and use of the sweeteners and caffeine disclaimers shortly after the warning labels were implemented. The sweetener disclaimer appears to be helping consumers modify their perceptions regarding industrialised beverages for children. Findings may help decision-makers improve the regulation and better target communication strategies.